Perceived Quality of Mobile Services A Segment-Specific Analysis - Dickinger, Astrid (Forschungsergebnisse der Wirtschaftsuniversitaet Wien, 2008)
The book investigates user satisfaction with mobile services, the perceived quality of m-commerce products, and the loyalty towards service providers. After introducing the m-commerce value chain and emerging mobile services, the first part examines relevant theories from diffusion of innovations and service quality to mobile services, and identifies new trends in the mobile communication market. The book demonstrates to what extent service quality and adoption theories of consumer behavior literature explain the (repeated) usage of mobile services, and how the results differ by user segments. A-priori and a-posteriori segmentations provide detailed insights. The results indicate that it is important to consider (un)observed heterogeneity in explanatory models.